Correlates of Immunity to Influenza as Determined by Challenge of Children with Live, Attenuated Influenza Vaccine. (23rd May 2016) - Wright, Peter F.; Hoen, Anne G.; Ilyushina, Natalia A.; Brown, Eric P.; Ackerman, Margaret E.; Wieland-Alter, Wendy; Connor, Ruth I.; Jegaskanda, Sinthujan; Rosenberg-Hasson, Yael; Haynes, Brenda C.; Luke, Catherine J.; Subbarao, Kanta; et al.
Abstract: Background.  The efficacy of live, attenuated live attenuated influenza vaccine(LAIV) and inactivated influenza vaccine(IIV) is poorly explained by either single or composite immune responses to vaccination. Protective biomarkers were therefore studied in response to LAIV or IIV followed by LAIV challenge in children. Methods.  Serum and mucosal responses to LAIV or IIV were analyzed using immunologic assays to assess both quantitative and functional responses. Cytokines and chemokines were measured in nasal washes collected before vaccination, on days 2, 4, and 7 after initial LAIV, and again after LAIV challenge using a 63-multiplex Luminex panel. Results.  Patterns of immunity induced by LAIV and IIV were significantly different. Serum responses induced by IIV, including hemagglutination inhibition, did not correlate with detection or quantitation of LAIV on subsequent challenge. Modalities that induced sterilizing immunity seen after LAIV challenge could not be defined by any measurements of mucosal or serum antibodies induced by the initial LAIV immunization. No single cytokine or chemokine was predictive of protection. Conclusions.  The mechanism of protective immunity observed after LAIV could not be defined, and traditional measurements of immunity to IIV did not correlate with protection against an LAIV challenge.